Strategi pengembangan kelapa sawit rakyat dalam pemulihan pascapandemi Covid-19 di Provinsi Sumatera Utara: Strategy for developing smallholder oil palm in the COVID-19 post-pandemic recovery in North Sumatra Province - Dani, Fatimatuz Zahro Diah Putri (Analisis Kebijakan Pertanian, 2025)
The plantation industry sector in Indonesia experienced significant adverse impacts due to the COVID-19 pandemic, particularly in the production of crude palm oil (CPO), one of the country’s leading export commodities. This study aims to analyze the internal and external factors that affect the marketing and trade of oil palm products produced by smallholders and to formulate appropriate strategies to support post-pandemic recovery. A mixed-methods approach was employed, utilizing a concurrent triangulation design through focus group discussions and in-depth interviews to identify internal and external factors. These factors were then analyzed using SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis. North Sumatra Province was selected as the study location as it is the second-largest oil palm-producing province in Indonesia. Respondents in this study were limited to non-ISPO (Indonesian Sustainable Palm Oil) smallholder farmers. The analysis revealed that the priority strategy to be implemented is the optimization strategy (S–O) with a score of 3.28. This strategy involves utilizing agricultural production facilities, improving access to information and services, and enhancing product quality, all of which are supported by adequate infrastructure and agricultural output distribution systems. The study concludes that the strategy to strengthen the competitiveness of smallholder oil palm needs to be directed toward achieving synergy between actors and enhancing the overall capacity of farmers as a whole. The policy implication of this study is the need to prioritize the collaborative development of smallholder downstream palm oil industries and the application of mechanization-based Good Agricultural Practices (GAPs) in cultivation and processing.